Maturation of blood vessels by haematopoietic stem cells and progenitor cells: Involvement of apelin/APJ and angiopoietin/Tie2 interactions in vessel caliber size regulation - Takakura, Nobuyuki; Kidoya, Hiroyasu (Thrombosis and Haemostasis, 2009)
Apelin is a recently-isolated bioactive peptide from bovine gastric extract. The gene encodes a protein of 77 amino acids, which can generate two active polypeptides, long (42–77) and short (65–77). Both peptides ligate and activate APJ, a G protein-coupled receptor expressed in the cardiovascular and central nervous systems. Although an essential role for the apelin/APJ system in blood vessel formation has been reported in Xenopus, its precise function in mammals is unclear. Blood vessel tube formation is accomplished by two main mechanisms: 1) single cell hollowing, in which a lumen forms within the cytoplasm of a single endothelial cell (EC), and 2) cord hollowing in which a luminal cavity is created de novo between ECs in a thin cylindrical cord. Molecular control of either single cell or cord hollowing has not been precisely determined. Angiopoietin-1 (Ang1) has been reported to induce enlargement of blood vessels. Apelin is produced from ECs upon activation of Tie2, a cognate receptor of Ang1, expressed on ECs. It has been suggested that apelin induces cord hollowing by promoting proliferation and aggregation/assembly of ECs. During angiogenesis, haematopoietic stem cells (HSCs) and progenitor cells (HPCs) are frequently observed in the perivascular region. They produce Ang1 and induce migration of ECs, resulting in a fine vascular network. Moreover, HSCs/HPCs can induce apelin production from ECs. Therefore, this review article posits that HSCs/HPCs regulate caliber size of blood vessels via apelin/APJ and Angiopoietin/Tie2 interactions.
Keywords: Haematopoietic stem cell; haematopoietic progenitor cells; Tie2; Angiopoietin-1; Apelin, APJ